Determinants of Mobile Investment Platform Adoption for Islamic Mutual Fund Investing - Dzakirah, Hanin Dzikra; Septiarini, Dina Fitrisia (Universitas Airlangga, 2024)
This study aims to identify the factors that influence the intention to use the Bibit application for Islamic mutual fund investments among Generation Z by employing variables from the Unified Theory of Acceptance and Use of Technology (UTAUT), perceived trust, and personal innovativeness. The results indicate that performance expectancy, social influence, perceived trust, and personal innovativeness significantly influence the intention to use. In contrast, effort expectancy and facilitating conditions do not have a significant effect on the intention to use. This study is limited by its sample size, focusing only on Generation Z, who are known for their technological affinity. Nevertheless, the findings are expected to benefit investment companies, particularly Bibit.id, in developing marketing strategies and considering factors that influence user intention. Furthermore, the results can provide insights into creating features and services better suited to the needs of Generation Z. Theoretically, this study is expected to contribute knowledge, particularly in the Islamic finance industry, specifically in the area of Islamic mutual funds.